2019
DOI: 10.4236/jtr.2019.73017
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Outcome of Childhood Tuberculosis Seen at the University of Port Harcourt Teaching Hospital, Nigeria

Abstract: Background: Despite the fact that Tuberculosis (TB) is preventable, treatable and curable, it has remained a significant cause of childhood morbidity and mortality. Identifying patterns of TB and its treatment outcome which is the aim of this study is relevant for TB control programmes. Methodology: This was a retrospective cross-sectional study carried out over a three-month period from April-June 2019 at the directly observed treatment Short course (DOTS) clinic of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It found that there was no difference in treatment outcome of TB among different subgroups of EPTB (TB lymphadenitis and pleural effusion). This was in line with the study conducted in Nigeria ( 33 ). But this different with study conducted in Kinshasa Zaire which reported low treatment rate completion among children with TB lymph node (67.8%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…It found that there was no difference in treatment outcome of TB among different subgroups of EPTB (TB lymphadenitis and pleural effusion). This was in line with the study conducted in Nigeria ( 33 ). But this different with study conducted in Kinshasa Zaire which reported low treatment rate completion among children with TB lymph node (67.8%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%